Insider-led privatization in Poland, Russia and Lithuania : a comparison - Kalmi, Panu (Idäntalouksien katsauksia, 1995)
The purpose of this study is to compare insider privatization in three countries.Two problems the author faced should be noted.First, whereas in Russia and in Lithuania insider ownership was an important element in all privatization, in Poland it was in practice limited to relatively small enterprises".The second problem was that the material the author obtained on Lithuanian privatization did not allow for farreaching comparisons.Lithuanian privatization is dealt with separately, but many of the findings in section 3 are probably applicable to Lithuanian privatization as well. In section 2 we evaluate privatization policies in the countries in our survey and examine how insider participation was arranged in these countries.In section 3 insider control is evaluated in more detail.Section 4 concludes the study.
Keywords: yksityistäminen; Puola; Venäjä; Liettua; Bofit-kokoelma; SP